Novel Emergency Medicine Curriculum Utilizing Self-Directed Learning and the Flipped Classroom Method: Gastrointestinal Emergencies Small Group Module - Andrew King; Elizabeth Matheson; Christopher San Miguel; Sarah Greenberger; Michael Barrie; Jillian McGrath; Howard Werman; Ashish Panchal; Daniel Martin; David P Bahner; Sorabh Khandelwal; Jennifer Mitzman (eScholarship Publishing, University of California, 2017)
Audience and type of curriculum: This curriculum created and implemented at The Ohio State University Wexner Medical Center was designed to educate our emergency medicine (EM) residents, PGY-1 to PGY-3, as well as medical students and attending physicians. Introduction/Background: Gastrointestinal (GI) emergencies comprise approximately 12% of emergency department (ED) visits.1 Residents must be proficient in the differential diagnosis and management of the wide variety of GI emergencies. The flipped classroom curricular model emphasizes self-directed learning activities completed by learners, followed by small group discussions pertaining to the topic reviewed. The active learning fostered by this curriculum increases faculty and learner engagement and interaction time typically absent in traditional lecture-based formats.2-4 Studies have revealed that the application of knowledge through case studies, personal interaction with content experts, and integrated questions are effective learning strategies for emergency medicine residents.4-6 The Ohio State University EM Residency didactic curriculum recently transitioned to a "flipped classroom" approach.7-10 We created this innovative curriculum aimed to improve our residency education program and to share educational resources with other EM residency programs. This proposed curriculum utilizes an 18-month curricular cycle. The flipped classroom curriculum maximizes didactic time and resident engagement, fosters intellectual curiosity and active learning, and meets the needs of today's learners. 3,6,11 Objectives: We aim to teach the presentation and management of GI emergencies through the creation of a flipped classroom design. This unique, innovative curriculum utilizes resources chosen by education faculty and resident learners, study questions, real-life experiences, and small group discussions in place of traditional lectures. In doing so, a goal of the curriculum is to encourage self-directed learning, improve understanding and knowledge retention, and improve the educational experience of our residents. Methods: The educational strategies used in this curriculum include: small group modules authored by education faculty and content experts, based on core emergency medicine content. This program also includes resident submitted questions that were developed during review of the content. The Socratic Method, used during small group sessions encourages active participation; small groups also focus on synthesis and application of knowledge through discussion of real life experiences. The use of free open access medical education (FOAM) resources allows learners to work at their own pace and maximize autonomy in resident learning.